Змістова характеристика функціонування регіональних ринків нерухомості - Павлов, Костянтин Володимирович; Pavlov, Kostiantyn V. (Східноєвропейський національний університет ім. Лесі Українки, 2017)
В статті розглянуто наукові підходи до сутності «регіонального ринку нерухомості», опрацьована чимала кількість наукових праць, уніфіковані основні положення та твердження щодо змістовного визначення поняття «регіональний ринок нерухомості». Визначено структуру та суб’єктну взаємодію на регіональних ринках нерухомості, охарактеризовано організаційно економічний механізм його функціонування. Запропоновані особливі підходи до регулювання ринків нерухомості на основі їх регіональних особливостей.

In article scientific approaches to the essence «of the regional real estate market», worked out a considerable number of scientific publications standardized basic provisions and statements regarding meaningful definition of «local real estate market». The structure and subjective engagement in regional real estate markets, describes the organizational and economic mechanism of its operation. The proposed specific approaches to the regulation of real estate markets based on their regional characteristics. In conditions of deepening subject relations and market transformation process is systematic grouping of markets in national, regional and global scales. The smallest regional market system is the grouping of certain activities, goods and their institutional support. One of the important features of the regional grouping is the real estate market, whose facilities are an important component of national wealth and is characterized by the specificity of regulation and interaction between actors. The establishment and effective functioning of regional real estate markets is the key to successful development of local and regional governance, and prosperity of the region as a whole. Despite all investments in real estate remains one of the reliable ways of economic actors. Payback period of investment in commercial real estate in Ukraine is 4−7 years, whereas in Europe 10−20 years, and that significant benefits. The risk is relatively low due to the unlimited lifetime of the building. Based on the analysis should consider the following suggestions, which significantly affect the activities of regional real estate markets, namely to reduce the construction time to improve the quality of residential or commercial conditions, reduce operating costs, energy and environmental pollution; use alternative national (cheap) building materials and innovative technologies to reduce the cost of 1 sq. m. of housing; creating a single information base of the market; operation of a special fund reserve and guarantee of the existence of housing; standardize approaches to assessing real property (real estate) within functioning regional real estate markets.
Content Description of the Functioning of Regional Real Estate Markets
Keywords: об’єкти нерухомості; локальні ринки; регіональні ринки; національні ринки; попит; пропозиція; еластичність; суб’єкти ринку; real estate; local markets; national markets; regional markets; demand; supply; elasticity; market actors